Method for making chalcogenide glass material

A low-oxygen chalcogenide glass material with improved infrared transmittance and processability addresses the limitations of crystalline materials, enhancing sensitivity and miniaturization in infrared sensors.

JP2024174089AActive Publication Date: 2024-12-13NIPPON ELECTRIC GLASS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024169004
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-03-28
Filing Date
2024-09-27
Publication Date
2024-12-13
Estimated Expiration
2038-10-17

AI Technical Summary

Technical Problem

Chalcogenide glass materials used in infrared sensors suffer from reduced infrared transmittance and are difficult to process into complex shapes due to crystalline materials like Ge and ZnSe, hindering mass production and miniaturization.

Method used

A chalcogenide glass material with an oxygen content of 100 ppm or less is developed, ensuring minimal infrared absorption and improved processability, allowing for the production of optical elements with reduced striae and enhanced infrared transmittance.

Benefits of technology

The glass material achieves high infrared transmittance and suitability for infrared sensors, enabling better sensitivity and miniaturization of infrared sensors by suppressing infrared absorption and image distortion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174089000001_ABST
    Figure 2024174089000001_ABST
Patent Text Reader

Abstract

To provide a glass that has excellent infrared transmittance and is suitably used for an infrared sensor.SOLUTION: A chalcogenide glass material has an oxygen content of 100 ppm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a chalcogenide glass material used in infrared sensors, infrared cameras, and the like. [Background technology]

[0002] In-vehicle night vision and security systems are equipped with infrared sensors used for detecting living organisms at night. Infrared sensors detect infrared rays with wavelengths of approximately 8 to 14 μm emitted from living organisms, so optical elements such as filters and lenses that transmit infrared rays in that wavelength range are provided in front of the sensor unit.

[0003] Materials for such optical elements include Ge and ZnSe. These are crystalline materials, so they are difficult to process and are difficult to process into complex shapes such as aspherical lenses. This makes them difficult to mass-produce, and it is also difficult to miniaturize infrared sensors.

[0004] In view of this, chalcogenide glass has been proposed as a glassy material that transmits infrared rays with wavelengths of about 8 to 14 μm and is relatively easy to process (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2009-161374 A Summary of the Invention [Problem to be solved by the invention]

[0006] The glass described in Patent Document 1 has a significantly reduced infrared transmittance at wavelengths of 10 μm or more, and therefore has poor sensitivity particularly to infrared radiation emitted from living organisms, and there is a risk that the infrared sensor will not function satisfactorily.

[0007] In view of the above, an object of the present invention is to provide a glass that has excellent infrared transmittance and is suitable for use in infrared sensors. [Means for solving the problem]

[0008] The present inventors conducted various studies, and obtained the following findings, which led them to propose the present invention. Chalcogenide glass materials are usually produced by putting raw materials into a quartz tube, evacuating it, and then melting it in a sealed state. However, even if high-purity raw materials are used, the surface of the raw materials is oxidized, and oxygen is mixed into the glass as an impurity, and the oxygen bonds with the components in the glass. As a result, the bonds have an absorption peak in the infrared range, and the infrared transmittance is likely to decrease.

[0009] That is, the chalcogenide glass material of the present invention is characterized in that the oxygen content is 100 ppm or less. By restricting the oxygen content, which causes a decrease in infrared transmittance, as described above, absorption in the infrared range is less likely to occur, and the decrease in infrared transmittance can be suppressed.

[0010] The chalcogenide glass material of the present invention preferably contains Te+S+Se (>0-100%).

[0011] The chalcogenide glass material of the present invention preferably contains, in mol %, 20 to 90% of Te.

[0012] The chalcogenide glass material of the present invention preferably contains, in mol %, more than 0 to 50% of Ge+Ga+Sb+As.

[0013] The chalcogenide glass material of the present invention preferably contains, in mol %, 0 to 50% Ag.

[0014] The chalcogenide glass material of the present invention preferably contains, in mol %, 0 to 50% of Si.

[0015] The chalcogenide glass material of the present invention preferably does not have striae with a length of 500 μm or more in the glass material.

[0016] The optical element of the present invention is characterized by using the above-mentioned chalcogenide glass material.

[0017] The infrared sensor of the present invention is characterized by using the above optical element. Effect of the Invention

[0018] According to the present invention, it is possible to provide a chalcogenide glass material that has excellent infrared transmittance and is suitable as an optical element for an infrared sensor. [Brief description of the drawings]

[0019] [Figure 1] 1 is a graph showing infrared transmittance curves for Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The oxygen content of the chalcogenide glass material of the present invention is 100 ppm or less, preferably 50 ppm or less, 20 ppm or less, 15 ppm or less, 12 ppm or less, 10 ppm or less, 8 ppm or less, 5 ppm or less, 3 ppm or less, and particularly preferably 1 ppm or less. If the oxygen content is too high, absorption in the infrared region is likely to occur and the infrared transmittance is likely to decrease. The lower limit of the oxygen content is not particularly limited, but in reality it is 0.01 ppm or more.

[0021] The bonded portion between oxygen and components in the glass is prone to change the refractive index and to form striae, but the chalcogenide glass material of the present invention has a low oxygen content, so oxygen is less likely to bond with components in the glass and striae are less likely to form. Specifically, the chalcogenide glass material of the present invention is preferably free of striae with a length of 500 μm or more. Even if striae are present in the chalcogenide glass material, their length is preferably less than 500 μm, 200 μm or less, 100 μm or less, 50 μm or less, and particularly 10 μm or less. In this way, when used as an optical element, it is possible to suppress a decrease in resolution caused by image distortion or disturbance.

[0022] The chalcogenide glass material of the present invention has a low oxygen content as described above, so oxygen is less likely to bond with components in the glass. Specifically, Ge-O bonds (13.0 μm), Se-O bonds (11.0 μm), As-O bonds (12.7 μm), Si-O bonds (8.9 μm, 14.2 μm), Ga-O bonds (17.5 μm), and the like, which have absorption peaks in the infrared region, are less likely to form, making it easier to suppress a decrease in infrared transmittance.

[0023] The composition of the chalcogenide glass material of the present invention will be described below. In the following description of the content of each component, "%" means "mol %" unless otherwise specified.

[0024] The chalcogen elements Te, S, and Se are components that form a glass skeleton. The content of Te+S+Se (the total content of Te, S, and Se) is preferably more than 0 to 100%, 20 to 90%, 30 to 8%, 40 to 85%, 45 to 82%, 50 to 80%, 55 to 80%, 60 to 80%, 65 to 80%, and particularly preferably 70 to 80%. If the content of Te+S+Se is too low, vitrification becomes difficult. If the content of Te+S+Se is too high, the glass components are likely to evaporate during melting, which is likely to cause striae. From the viewpoint of suppressing the occurrence of such defects, the content of Te+S+Se is preferably 90% or less.

[0025] The preferred ranges of the contents of Te, S and Se are as follows:

[0026] Among Te, S, and Se, Te is most preferable because it allows infrared transmission up to longer wavelengths. The content of Te is preferably 20 to 90%, 30 to 88%, 40 to 85%, 45 to 82%, 50 to 80%, 55 to 80%, 60 to 80%, 65 to 80%, and particularly preferably 70 to 80%. If the content of Te is too low, vitrification becomes difficult. On the other hand, if the content of Te is too high, Te-based crystals are precipitated, making it difficult for infrared rays to transmit.

[0027] The S content is preferably 0 to 90%, 10 to 90%, 20 to 88%, 30 to 85%, 40 to 82%, 50 to 80%, 55 to 80%, 60 to 80%, 65 to 80%, and particularly preferably 70 to 80%.

[0028] The Se content is preferably 0 to 90%, 10 to 90%, 20 to 88%, 30 to 85%, 40 to 82%, 50 to 80%, 55 to 80%, 60 to 80%, 65 to 80%, and particularly preferably 70 to 80%.

[0029] Ge, Ga, Sb, and As are components that broaden the vitrification range and increase the thermal stability of glass (vitrification stability). The content of Ge+Ga+Sb+As (total amount of Ge, Ga, Sb, and As) is preferably more than 0 to 50%, 10 to 45%, 15 to 43%, 20 to 43%, 25 to 43%, and particularly preferably 30 to 43%. If the content of Ge+Ga+Sb+As is too low or too high, vitrification becomes difficult.

[0030] The Ge+Ga content (the total amount of Ge and Ga) is preferably 0 to 40%, 2 to 35%, 4 to 33%, 4 to 30%, or 4 to 28%, and particularly preferably 4 to 25%.The Sb+As content (the total amount of Sb and As) is preferably 0 to 45%, 5 to 40%, 10 to 35%, or 15 to 35%, and particularly preferably 20 to 35%.

[0031] The preferred ranges of the contents of Ge, Ga, Sb, and As are as follows:

[0032] The Ge content is preferably 0 to 40%, 2 to 35%, 4 to 33%, 4 to 30%, or 4 to 28%, and particularly preferably 4 to 25%.

[0033] The Ga content is preferably 0 to 40%, 2 to 35%, 4 to 33%, 4 to 30%, or 4 to 28%, and particularly preferably 4 to 25%.

[0034] The Sb content is preferably 0 to 45%, 5 to 40%, 10 to 35%, or 15 to 35%, and particularly preferably 20 to 35%.

[0035] The As content is preferably 0 to 45%, 5 to 40%, 10 to 35%, or 15 to 35%, and particularly preferably 20 to 35%.

[0036] Ag is an essential component for increasing the thermal stability (vitrification stability) of glass. The Ag content is preferably 0 to 50%, more than 0 to 50%, 1 to 45%, 2 to 40%, 3 to 35%, 4 to 30%, 5 to 25%, and particularly preferably 5 to 20%. If the Ag content is too high, vitrification becomes difficult.

[0037] Silicon is an essential component for increasing the thermal stability (vitrification stability) of glass. The silicon content is preferably 0 to 50%, more than 0 to 50%, 1 to 45%, 2 to 40%, 3 to 35%, 4 to 30%, 5 to 25%, and particularly preferably 5 to 20%. If the silicon content is too high, infrared absorption due to silicon is likely to occur, making it difficult for infrared rays to pass through.

[0038] Al, Ti, Cu, In, Sn, Bi, Cr, Sb, Zn, and Mn are components that enhance the thermal stability (vitrification stability) of glass without reducing the infrared transmission properties. The content of Al+Ti+Cu+In+Sn+Bi+Cr+Sb+Zn+Mn (the total content of Al, Ti, Cu, In, Sn, Bi, Cr, Sb, Zn, and Mn) is preferably 0 to 40%, 2 to 35%, 4 to 30%, and particularly preferably 5 to 25%. If the content of Al+Ti+Cu+In+Sn+Bi+Cr+Sb+Zn+Mn is too high, vitrification becomes difficult. The contents of each of Al, Ti, Cu, In, Sn, Bi, Cr, Sb, Zn, and Mn are preferably 0 to 40%, 1 to 40%, 1 to 30%, 1 to 25%, and particularly preferably 1 to 20%, respectively. Among these, it is preferable to use Al, Cu or Sn, since they have a particularly large effect of increasing the thermal stability of the glass.

[0039] F, Cl, Br, and I are also components that enhance the thermal stability (vitrification stability) of glass. The content of F+Cl+Br+I (total amount of F, Cl, Br, and I) is preferably 0-40%, 2-35%, 4-30%, and particularly 5-25%. If the content of F+Cl+Br+I is too high, vitrification becomes difficult and weather resistance is likely to decrease. The contents of each of the components F, Cl, Br, and I are preferably 0-40%, 1-40%, 1-30%, 1-25%, and particularly 1-20%, respectively. Among them, I is preferable in that an elemental raw material can be used and it has a particularly large effect of enhancing the thermal stability of glass.

[0040] In addition to the above components, P, Pb, Tl, etc. may be contained within a range that does not impair the effects of the present invention. Specifically, the content of each of these components is preferably 0 to 5%, and more preferably 0 to 2%.

[0041] The chalcogenide glass material of the present invention can be produced, for example, as follows. The raw materials are mixed to obtain the above glass composition, and a raw material batch is obtained. Next, after evacuating the quartz glass ampoule while heating it, the raw material batch is placed in it, and the quartz glass ampoule is sealed with an oxygen burner while introducing a reducing gas into the quartz glass ampoule. Next, the sealed quartz glass ampoule is heated to 650-1000°C at a rate of 10-40°C / hour in a melting furnace, and then held for 6-12 hours. During the holding time, if necessary, the quartz glass ampoule is turned upside down and the melt is stirred. In this way, by melting the raw materials in the reducing gas, oxygen in the raw materials is removed, making it easier to obtain glass with a low oxygen content. Here, N2-H2 mixed gas, CO, H2S, N2O, SO2, NH3, etc. can be used as the reducing gas, but it is preferable to use N2-H2 mixed gas because it is inexpensive and safe.

[0042] The quartz glass ampoule is then removed from the melting furnace and rapidly cooled to room temperature in a reducing gas to obtain the chalcogenide glass material of the present invention.

[0043] If a reducing gas atmosphere is created inside the melting furnace, the quartz glass ampoules can be melted without being sealed, making it possible to continuously melt glass with a low oxygen content.

[0044] Furthermore, a reducing gas may be bubbled into the molten glass. The glass can be stirred by bubbling, which can promote homogenization of the glass. As a result, the occurrence of striae can be suppressed.

[0045] The chalcogenide glass material thus obtained can be processed into a predetermined shape (disk, lens, etc.) to produce an optical element.

[0046] For the purpose of improving the transmittance, an anti-reflection film may be formed on one or both sides of the optical element. Examples of the method for forming the anti-reflection film include a vacuum deposition method, an ion plating method, and a sputtering method.

[0047] After the anti-reflection film is formed on the chalcogenide glass material, it may be processed into a predetermined shape. However, since the anti-reflection film is likely to peel off during the processing step, it is preferable to form the anti-reflection film after processing the chalcogenide glass material into a predetermined shape unless there are special circumstances.

[0048] The chalcogenide glass material of the present invention has excellent infrared transmittance and is therefore suitable for use as a cover member for protecting the sensor portion of an infrared sensor, or as an optical element such as a lens for focusing infrared light on the infrared sensor portion. EXAMPLES

[0049] The present invention will be described below based on examples, but the present invention is not limited to these examples.

[0050] Tables 1 to 4 show Examples 1 to 35 of the present invention and Comparative Example 1.

[0051] [Table 1]

[0052] [Table 2]

[0053] [Table 3]

[0054] [Table 4]

[0055] The samples of Examples 1 to 34 were prepared as follows. After evacuating a quartz glass ampoule while heating it, a raw material batch prepared to obtain the glass composition shown in the table was placed in the quartz glass ampoule. Next, the quartz glass ampoule was sealed with an oxygen burner while introducing N2-H2 gas into the quartz glass ampoule. Next, the sealed quartz glass ampoule was heated to 650 to 1000°C at a rate of 10 to 40°C / hour in a melting furnace, and then held for 6 to 12 hours. During the holding time, the quartz gas ampoule was turned upside down to stir the molten material. Next, the quartz glass ampoule was removed from the melting furnace and rapidly cooled to room temperature to obtain a sample.

[0056] The sample of Example 35 was prepared as follows. A raw material batch prepared to obtain the glass composition shown in the table was placed in a quartz glass ampoule. Next, in a melting furnace into which N2-H2 gas was introduced, the unsealed quartz glass ampoule was heated to 750°C at a rate of 40°C / hour and held at this temperature for 6 hours. The quartz glass ampoule was then removed from the melting furnace and rapidly cooled to room temperature to obtain a sample.

[0057] In Comparative Example 1, a sample was prepared in the same manner as in Example 1, except that N2-H2 gas was not introduced.

[0058] The oxygen content of the obtained samples was measured using an oxygen analyzer (LECO Japan ONH836). In addition, infrared transmittance was measured at a thickness of 2 mm to confirm the presence or absence of an absorption peak in the infrared region. Furthermore, the obtained samples were internally observed by a shadowgraph method using infrared light with a wavelength of 10 μm to confirm the presence or absence of striae with a length of 500 μm or more. The results are shown in Tables 1 to 4. In addition, infrared transmittance curves for Example 1 and Comparative Example 1 are shown in FIG.

[0059] As is clear from Tables 1 to 4 and Figure 1, the samples of Examples 1 to 35 had a low oxygen content of 0.1 to 1.4 ppm in the glass, had no absorption peak in the infrared region, and had excellent homogeneity with no striae having a length of 500 μm or more.

[0060] On the other hand, the sample of Comparative Example 1 had an oxygen content of 123 ppm and had an absorption peak at about 17.5 μm. From the position of the absorption peak, it is considered that the absorption peak is caused by Ga-O bonds. In addition, striae with a length of 500 μm or more were confirmed. [Industrial Applicability]

[0061] The infrared transmitting glass of the present invention is suitable for use as a cover member for protecting the sensor section of an infrared sensor, or as an optical element such as a lens for focusing infrared light on the sensor section.

Claims

1. A chalcogenide glass material having an oxygen content of 100 ppm or less.

2. 2. The chalcogenide glass material according to claim 1, characterized in that it contains, in mol %, Te+S+Se (>0-100%).

3. 3. The chalcogenide glass material according to claim 1, further comprising, in mol %, 20 to 90% of Te.

4. 4. The chalcogenide glass material according to claim 1, characterized in that it contains, in mol %, more than 0 to 50% of Ge+Ga+Sb+As.

5. 5. The chalcogenide glass material according to claim 1, containing, in mol %, 0 to 50% Ag.

6. 6. The chalcogenide glass material according to claim 1, which contains, in mol %, 0 to 50% of Si.

7. 7. The chalcogenide glass material according to claim 1, wherein the glass material is free of striae having a length of 500 μm or more.

8. An optical element comprising the chalcogenide glass material according to any one of claims 1 to 7.

9. An infrared sensor comprising the optical element according to claim 8.

Citation Information

Patent Citations

  • Production of chalcogenide glass

    JP1988218518A

  • Production of clad glass tube for chalcogenide glass fiber

    JP1988230532A

  • Infrared-transmitting glass and production thereof

    JP1993004835A

  • Infrared transmitting glass

    JP2017057110A

  • Glass, method for producing glass, and optical element

    WO2017168939A1